A Study of Online Learning Studies in Natural Sciences Subject in Biology Topic during the Covid-19 Pandemic - Fatma N. Utina; Ani M. Hasan; Djuna Lamondo (Postgraduate, University of Mataram, 2022)
Online learning is one of the efforts made by the government in the education sector to prevent the spread of Covid-19 in Indonesia. The purpose of this study is to determine the implementation of the application of online learning to science lessons in biology material during the Covid-19 pandemic. This research method is descriptive. The results showed that the implementation of online learning of Biology Science material class VIII MTs in Gorontalo City in the teacher aspect included strong criteria as seen from 5 indicators, namely online learning tools, online learning processes, student participation in online learning, online practicum implementation and the assessment process. The implementation of online learning on the material of Biology Science class VIII MTs in Gorontalo City on student aspects includes strong criteria as can be seen from 4 indicators, namely the online learning process, student participation in online learning, implementation of online practicum and increasing creativity. Thus, it can be concluded that the implementation of online learning of biology science material class VIII MTs in Gorontalo City is a strong criterion.